NUTRIENTS REQUIREMENT OF SPINACH IN POTATO-SPINACH SEQUENCE IN MID-HILLS OF HIMACHAL PRADESH - Dua, V. K.; Lal, S S. (Potato Journal, 2013)
Present investigation was undertaken at Shimla in potato-spinach sequence to workout the FYM and nitrogen requirements of spinach. The potato crop was supplied with recommended doses of FYM and NPK (30 t FYM/ha and 150, 100 and 100 kg/ha of N, P2O5 and K2O kg/ha, respectively). Two levels of FYM (0 and 10 t/ha) and three levels of nitrogen (25, 50 and 75 kg/ha) were tested on subsequent spinach crop. Results revealed that spinach required only 2/3rd nitrogen (50 kg/ha) and full FYM (10 t/ha) for optimum yield if the preceding potato received recommended doses of FYM and NPK.